Patterns of Lecturer and Student Speech Acts in EFL Classroom Interaction: Qualitative Study Insights - Rahmi R; Uswatunnisa; Rina Marliana (New Language Dimensions, 2025)
Classroom interaction has long been a significant concern in English as a Foreign Language (EFL) education, particularly the persistent imbalance in participation, in which lecturers dominate classroom discourse while students make minimal contributions. Within the international discussion of interactional asymmetry and learner agency, speech act theory offers a valuable lens for examining how such interactional roles are constructed and maintained in the classroom environment. The findings indicate that classroom interactions are heavily dominated by representative and directive speech acts from lecturers, which serve to explain content and organize learning activities. In contrast, students produce only limited expressive responses, indicating limited opportunities to engage in various pragmatic roles. Commissive and declarative speech acts are absent, reflecting students' limited role in the meaning-making process. The prevalence of these patterns is shaped by pedagogical strategies, interlocutor roles, peer dynamics, and activity types, as well as student affective factors such as self-confidence and anxiety. By highlighting patterns of pragmatic dominance and their contextual determinants, this study extends research on international EFL classroom interaction beyond descriptive classification. It highlights how the distribution of speech acts reflects broader pedagogical and psychological dimensions, offering insights for fostering more interactionally balanced and student-centered EFL learning environments.